Elevated CO2 increases glomalin-related soil protein (GRSP) in the rhizosphere of Robinia pseudoacacia L. seedlings in Pb- and Cd-contaminated soils. (November 2016) - Jia, Xia; Zhao, Yonghua; Liu, Tuo; Huang, Shuping; Chang, Yafei
Abstract: Glomalin-related soil protein (GRSP), which contains glycoproteins produced by arbuscular mycorrhizal fungi (AMF), as well as non-mycorrhizal-related heat-stable proteins, lipids, and humic materials, is generally categorized into two fractions: easily extractable GRSP (EE-GRSP) and total GRSP (T-GRSP). GRSP plays an important role in soil carbon (C) sequestration and can stabilize heavy metals such as lead (Pb), cadmium (Cd), and manganese (Mn). Soil contamination by heavy metals is occurring in conjunction with rising atmospheric CO2 in natural ecosystems due to human activities. However, the response of GRSP to elevated CO2 combined with heavy metal contamination has not been widely reported. Here, we investigated the response of GRSP to elevated CO2 in the rhizosphere of Robinia pseudoacacia L. seedlings in Pb- and Cd-contaminated soils. Elevated CO2 (700 μmol mol −1 ) significantly increased T- and EE- GRSP concentrations in soils contaminated with Cd, Pb or Cd + Pb. GRSP contributed more carbon to the rhizosphere soil organic carbon pool under elevated CO2  + heavy metals than under ambient CO2 . The amount of Cd and Pb bound to GRSP was significantly higher under elevated (compared to ambient) CO2 ; and elevated CO2 increased the ratio of GRSP-bound Cd and Pb to total Cd and Pb. However, available Cd and Pb in rhizosphere soil under increased elevated CO2 compared to ambient CO2 . The combination of both metals and elevated CO2 led to a significant increase in available Pb in rhizosphere soil compared to the Pb treatment alone. In conclusion, increased GRSP produced under elevated CO2 could contribute to sequestration of soil pollutants by adsorption of Cd and Pb. Graphical abstract: Highlights: Elevated CO2 increased GRSP contents in the rhizosphere under Cd and Pb stress. Elevated CO2 increased the amount of GRSP-bound Cd and Pb. Elevated CO2 improved the ratio of GRSP-bound Cd and Pb to total Cd and Pb. Increased GRSP under elevated CO2 contributed to metal sequestration in soil. Abstract : Increased GRSP produced under elevated CO2 could contribute to sequestration of soil pollutants via adsorption of Cd and Pb.